Особливості формування вищої педагогічної освіти Італії в першій половині ХХ століття - Нелін, Євген (Studies in Comparative Education, 2014)
Стаття присвячена проблемі розвитку вищої педагогічної освіти Італії в період ХІХ–ХХ століття. Розкрито особливості становлення системи вищої освіти Італії шляхом реформування нормативно-правової бази. Розглянута еволюція становлення національної системи освіти Італії на базі освітніх систем Англії, Німеччини та Франції. Підкреслено динаміку розвитку вищої педагогічної освіти Італії в період світових війн. Показано вплив Національної фашистської партії на систему управління вищими навчальними закладами. Зроблено висновок, що сектор вищої університетської освіти в Італії, на середину ХХ століття, був представлений мережею елітних університетів. Вищі торгові, промислові та ремісничі школи, а також педагогічні училища та технікуми складали розширену мережу неуніверситетського сектора освіти. Статья посвящена проблеме развития высшего педагогического образования Италии в период ХІХ-ХХ веков. Раскрываются особенности становления системы высшего образования Италии путем реформирования нормативно-правовой базы. Рассматривается эволюция становления национальной системы образования Италии на базе образовательных систем Англии, Германии и Франции. Подчеркнуто динамику развития высшего педагогического образования Италии в период мировых войн. Отмечается влияние Национальной фашистской партии на систему управления высшими учебными заведениями. Сделано вывод, что сектор высшего университетского образования Италии, на средину ХХ века, был представлен сетью элитных университетов. Высшие торговые, промышленные и ремесленные школы, а также педагогические училища и техникумы формировали широкую сеть. The article is dedicated to the exploration of the higher pedagogical education in Italy during the XIX – XX centuries. There are the main particularities discovered in the course of forming of the higher education system in Italy through the reformation of its national legal basis. There is the evolution of national education system of Italy has been thoroughly examined on the basis of educational programs of England, Germany and France as well as marked the dynamics of the higher education system development’s in Italy in the period between the I and II World Wars. A special attention was paid to a role of the Catholic Church and its influence on formation of system of the higher education in Italy. There is also marked the impact of the National Fascist Party within the system of management of the higher educational institutions’ and analyzed the activities of the ministers’ of education of the Fascist governments’ and results of their reforms. It is concluded that the sector of the higher education in Italy in the mid of XX century was mainly characterized by the presence of centralized elite universities. Wide range of the non-univesity sector was formed from the higher commercial, industrial, craft school as well as pedagogical colleges and professional institutions.